(untitled) (Journal of the College of Basic Education, 2026)
The current research aims to identify emotional disclosure and the level of proactive behavior among middle school students, as well as finding significant differences in the variable according to gender and the relationship between the two variables. The sample consisted of (400) male and female students, distributed equally according to the gender variable The researcher prepared a scale to measure emotional disclosure after it was presented to a committee of experts to determine the validity of the items in measuring what he set out to measure, and he adopted the scale (Al-Makadami, 2024). for proactive behavior, and the researcher concluded that middle school students have a high level of emotional disclosure and proactive behavior, and there is no significant difference in the level for males and females.